The effect of washback on teaching methodology in distance education EFL - Elahe, Moradi; Ghabanchi, Zargham (Penerbit Universiti Kebangsaan Malaysia, 2017)
The notion of washback is a prominent concept in language teaching and testing. Examinations are considered to be powerful determiners of what goes on in classrooms and their results can play a significant role in setting educational standards of an institution. The connection between testing, teaching and learning is addressed by a number of terms. Washback is one that refers to the influence of tests on teaching and learning. The aim of this study was to investigate whether the centralized final examinations at Payame Noor University (PNU), Iran’s distance education university, had any washback effect on teaching methodology and if so what kind of washback it might take. After conducting the pilot study, data collection was conducted by using two questionnaires for both PNU students and professors. Data were analyzed through descriptive statistics, Chi-square test, independent t-test, and one-way ANOVA. The results indicated that PNU EFL final examinations have washback effect on teaching methodology and this washback effect is more positive than negative.